Pengaruh Capital Intensity, Profitabilitas, dan Leverage Terhadap Agresivitas Pajak Pada Perusahaan Subsektor Pertambangan Yang Terdaftar di Bursa Efek Indonesia - Rifda Kamila Nasution; Ledy Setiawati (AKUNTANSI 45, 2026)
This study aims to analyze the influence of capital intensity, profitability, and leverage on tax aggressiveness in mining sub-sector companies listed on the Indonesia Stock Exchange for the 2021-2024 period. This study uses a purposive sampling method with certain criteria so that 27 companies as the research sample with a four year observation. Thus, the total number of observations used in this study is 108 observations. Data analysis was carried out using panel data regression with the assistance of EViews 12 software. In this study, tax aggressiveness as the dependent variable, proxied through the Effective Tax Rate (ETR). The result of hypothesis test show that capital intensity does not have a significant effect on tax aggressiveness, suggesting that the level of corporate investment in fixed assets is not sufficient to significantly influence tax aggressiveness behavior. Profitability has a significant positive and significant effect on tax aggressiveness, indicating that higher profitability increases management incentives to engage in tax planning activities. Meanwhile, leverage has a negative and significant effect on tax aggressiveness. This finding indicates that increased us of leverage encourages firm to be more cautious in implementing tax policies due to interest payment obligations and stricter monitoring by creditors, thereby limiting managerial opportunistic behavior.